PENDIDIKAN KARAKTER DALAM BAHAN AJAR BAHASA ARAB KELAS 3 MADRASAH IBTIDA’IYAH KURIKUKULUM 2013 - Miftakhul Munif (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2018)
The Lesson of Arab language in Indonesia, is the real have been learned begund since early. Yet, this Lesson of Arab language considered lesson difficult and crucial. In other side, turn up one problem ground unrest author to write this theme. That is luster moral decadence in Indonesia youth some the last years, so supplies of early child with character of education and good akhlak is a duty. Therefore, planting character of edutation since early is important matter, if looking the phenomenon what happen some the last years. So, impersonating active from government by religion ministry, in the drafting and giving in the teaching materials books to student be based on 2013 Curriculum, notably Arab language is important to attention. Because, this matter as regard with nation requirement, is formation character of society presently.